The Response of Performance to Merger Strategy in Indonesian Banking Industry: Analyses on Bank Mandiri, Bank Danamon, and Bank Permata - Lestari, Murti; Arsyad, Lincolin (Gadjah Mada International Journal of Business, 2010)
This study analyzes the responses of performances of BankMandiri, Bank Danamon, and Bank Permata to merger strategy.This paper harnesses the quantitative approach with structuralbreak analysis method and impulse response function. Theplausible findings indicate that the merger of Bank Permataproduces a better performance response in comparison to theconsolidation of Bank Mandiri and the merger of Bank Danamon.The merger of Bank Permata does not result in performanceshocks, and the structural break does not prevail either. On theother hand, the consolidation of Bank Mandiri and the mergerof Bank Danamon result in structural breaks, particularly in thespread performance. In order to return to the stable position, themergers of Bank Mandiri and Bank Danamon require a longertime than does the merger of Bank Permata. This researchindicates that for large banks, the mergers and acquisitions(retaining one existing bank) will deliver a better performanceresponse than will the consolidations (no existing bank).Keywords: impulse response function; merger; structural break